(untitled) (Biological Sciences - PJSIR, 1999)
Carbonaceous deposits on naphtha reforming catalysts playa decisive role in limiting process performance. The deposits negatively affect catalyst activity, selectivity, and the production cycle of a semi regenerative reformer. The magnitude of negative effect of those deposits is directly proportional to their amount and complexity. Investigations on used reforming catalysts samples reveal that the amount and type (complexity ofthechemical nature) of carbonaceous deposits are directly proportional to the catalyst life on stream and the severity of operating conditions. In addition, the combustibility behavior of carbonaceous deposits on the catalyst samples taken from different reformers are found to be different. Optimal carbon removal, for in situ catalyst regeneration, requires that specific conditions be developed, based on the results of well designed and properly performed investigations of the amount and type of carbonaceous deposits.